The Effect of Long Suffering Diabetes Mellitus on Blood Ureum Levels - Tasya, Rabaika Monica; Fihiruddin, Fihiruddin; Pauzi, Iswari (THRIVE Health Science Journal, 2024)
Diabetes mellitus is a disease characterized by increasing blood sugar levels caused by defective insulin secretion or action. Increased levels of sugar in the blood have a direct impact on the blood vessels in the kidneys. Such as decreasing the function of the kidney, the disturbing kidney function will increase the level of urea in the blood.To find out whether there is an effect of long-suffering from Diabetes mellitus on blood urea levels. This research is analytical observational research with a cross-sectional approach. The samples used Diabetes mellitus patients with variations in length suffering of 1-3 years, 4-6 years, and > 6 years. Data were collected and analyzed using Kruskal Wallis non-parametric statistical test. The average blood urea level of Diabetes mellitus patients who suffer 1-3 years, 4-6 years, and > 6 years is 29.17 mg/dL, 53.25 mg/dL, and 118.11 mg/dL. The Kruskal Wallis test showed a significant value = 0.000 < 0.05 (Pα) which indicated that the duration of suffering from Diabetes mellitus affected increasing blood urea levels